Prospective cross‐sectional study using Poisson renewal theory to study phase singularity formation and destruction rates in atrial fibrillation (RENEWAL‐AF): Study design. Issue 4 (10th June 2020) - Quah, Jing; Dharmaprani, Dhani; Lahiri, Anandaroop; Schopp, Madeline; Mitchell, Lewis; Selvanayagam, Joseph B.; Perry, Rebecca; Chahadi, Fahd; Tung, Matthew; Ahmad, Waheed; Stoyanov, Nikola; Joseph, Majo X.; et al.
Abstract: Background: Unstable functional reentrant circuits known as rotors have been consistently observed in atrial fibrillation and are mechanistically believed critical to the maintenance of the arrhythmia. Recently, using a Poisson renewal theory‐based quantitative framework, we have demonstrated that rotor formation (λf ) and destruction rates (λd ) can be measured using in vivo electrophysiologic data. However, the association of λf and λd with clinical, electrical, and structural markers of atrial fibrillation phenotype is unknown. Methods: RENEWAL‐AF is a multicenter prospective cross‐sectional study recruiting adult patients with paroxysmal or persistent atrial fibrillation undergoing clinically indicated catheter ablation. Patients will undergo intraprocedural electrophysiologic atrial fibrillation mapping, with λf and λd to be determined from 2‐minute unipolar electrogram recordings acquired before ablation. The primary objective will be to determine the association of λf and λd as markers of fibrillatory dynamics with clinical, electrical, and structural markers of atrial fibrillation clinical phenotype, measured by preablation transthoracic echocardiogram and cardiac magnetic resonance imaging. An exploratory objective is the noninvasive assessment of λf and λd using surface ECG characteristics via a machine learning approach. Results: Not applicable. Conclusion: This pilot study will provide insight into the correlation between λf /λd with clinical, electrophysiological, and structural markers of atrial fibrillation phenotype and provide a foundation for the development of noninvasive assessment of λf /λd using surface ECG characteristics will help expand the use of λf /λd in clinical practice. Abstract : Using a Poisson renewal theory‐based quantitative framework, we have recently demonstrated that rotor formation and destruction rates in atrial fibrillation can be objectively quantified using in vino electrophysiological data. RENEWAL‐AF is a pilot prospective cross‐sectional study investigating the association between the rates of rotor formation and destruction with clinical, electrical and structural markers of AF phenotype.